2010
DOI: 10.1039/b921060a
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic delta values of molybdenum standard reference and prepared solutions measured by MC-ICP-MS: Proposition for delta zero and secondary references

Abstract: We report the isotopic composition of five molybdenum (Mo) standard reference solutions and four fractions from one of these solutions eluted through anion resin column relative to a sixth reference solution. The reference solutions were National Institute of Standards and Technology (NIST) SRM 3134 (lot#891307), Johnson Matthey Specpure (JMC)-Mo Sie (lot #602332B), JMC-Mo Wen (lot#13989C), Merck (lot#170334), Sigma-Aldrich (lot#207306) and Prolabo. Measurements were conducted using Isoprobe multi collector in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
66
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(73 citation statements)
references
References 23 publications
5
66
0
2
Order By: Relevance
“…The NIST SRM 3134 Mo solution has been proposed as a universal zero-delta reference material for expressing Mo isotope data in delta notation for natural samples (Wen et al 2010, Greber et al 2012, Goldberg et al 2013. As demonstrated by Greber et al (2012) and Goldberg et al (2013) (Dodson 1963).…”
Section: Received 23 Apr 15 -Accepted 10 Aug 15mentioning
confidence: 94%
“…The NIST SRM 3134 Mo solution has been proposed as a universal zero-delta reference material for expressing Mo isotope data in delta notation for natural samples (Wen et al 2010, Greber et al 2012, Goldberg et al 2013. As demonstrated by Greber et al (2012) and Goldberg et al (2013) (Dodson 1963).…”
Section: Received 23 Apr 15 -Accepted 10 Aug 15mentioning
confidence: 94%
“…Unfortunately, no internationally accepted reference material was available, and therefore each group used its own isotopic reference material. This problem has been recognized, and recently different reference materials have been analyzed relative to each other [251,252], including the material used as the best measurement for defining the Mo atomic weight (NIST SRM 3134) [253,254,258]. This material, which is an atomic spectrometry standard provided by NIST, has been proposed as an anchor point for the δ 98/95 Mo [251] 9 .…”
Section: /95mentioning
confidence: 99%
“…This problem has been recognized, and recently different reference materials have been analyzed relative to each other [251,252], including the material used as the best measurement for defining the Mo atomic weight (NIST SRM 3134) [253,254,258]. This material, which is an atomic spectrometry standard provided by NIST, has been proposed as an anchor point for the δ 98/95 Mo [251] 9 . Mean Ocean Molybdenum (MOMo) δ 98/95 Mo has been measured as +2.09 ± 0.07 ‰ relative to NIST SRM 3134 [252] by analysis of five IAPSO ampoules (four from the Atlantic and one from the Mediterranean).…”
Section: /95mentioning
confidence: 99%
“…Results are reliable and satisfied with the quality control criteria. a) The reference values of SG-2 and SG-3 are quoted from Wen et al [28].…”
Section: Sampling and Analytical Techniquesmentioning
confidence: 99%
“…Because there are few universally acknowledged Mo isotopic international standards, a latest calibrating NIST SRM 3134 solution recommend by Wen et al [28] was used as an internal reference standard. Meanwhile, Wen et al suggested that the current international internal isotope laboratory using various criteria, such as JMC, Merck, NIST SRM 3134, with its Mo isotopic composition is consistent within errors [28].…”
Section: Sampling and Analytical Techniquesmentioning
confidence: 99%